WEB ACCESSIBILITY TESTING FOR VISUALLY IMPAIRED USERS ON E-COMMERCE WEBSITES USING ACCESS MONITOR - Nascimento, Lays de Paiva; Caraça, Matheus Rodrigues; Molina, Mariangela Ferreira Fuentes (Revista Interface Tecnológica, 2023)
The digital age brought many facilities to the world and directly impacted the way in which retail companies work and sell their products. This evolution made it much clearer the difficulties that people with visual impairments have in accessing and interacting with the digital world. This work, in addition to introducing the importance of e-commerce in Brazil, defining what digital accessibility is and the difficulties that people with visual impairments face on the web, carried out digital accessibility tests in the five largest companies with Brazilian e-commerce according to the ranking of Sociedade Brasileira de Varejo e Consumo (SBVC), using the accessibility guidelines of the World Wide Web Consortium (W3C) through the Access Monitor tool.
Keywords: Visual Impairment; Accessibility; E-Commerce; W3C